Calretinin as a Marker for Premotor Neurons Involved in Upgaze in Human Brainstem - Adamczyk, Christopher; Strupp, Michael; Jahn, Klaus; Horn, Anja K. E. (Frontiers in Neuroanatomy, 2015)
Eye movements are generated by different premotor pathways. Damage to them can cause specific deficits of eye movements, such as saccades. For correlative clinico-anatomical post-mortem studies of cases with eye movement disorders it is essential to identify the functional cell groups of the oculomotor system in the human brain by marker proteins. Based on monkey studies, the premotor neurons of the saccadic system can be identified by the histochemical markers parvalbumin and perineuronal nets in humans. These areas involve the interstitial nucleus of Cajal (INC) and the rostral interstitial nucleus of the medial longitudinal fascicle (RIMLF), which both contain premotor neurons for upgaze and downgaze. Recent monkey and human studies revealed a selective excitatory calretinin-positive input to the motoneurons mediating upgaze, but not to those for downgaze. Three premotor regions were identified as sources of calretinin input in monkey: y-group, INC and RIMLF. These findings suggest that the expression pattern of parvalbumin and calretinin may help to identify premotor neurons involved in up- or downgaze. In a post-mortem study of five human cases without neurological diseases we investigated the y-group, INC and RIMLF for the presence of parvalbumin and calretinin positive neurons including their co-expression. Adjacent thin paraffin sections were stained for the aggrecan component of perineuronal nets, parvalbumin or calretinin and glutamate decarboxylase. The comparative analysis of scanned thin sections of INC and RIMLF revealed medium-sized parvalbumin positive neurons with and without calretinin coexpression, which were intermingled. The parvalbumin/calretinin positive neurons in both nuclei are considered as excitatory premotor upgaze neurons. Accordingly, the parvalbumin-positive neurons lacking calretinin are considered as premotor downgaze neurons in RIMLF, but may in addition include inhibitory premotor upgaze neurons in the INC as indicated by co-expression of glutamate decarboxylase in a subpopulation. Calretinin-positive neurons ensheathed by perineuronal nets in the human y-group are considered as the homologue premotor neurons described in monkey, projecting to superior rectus and inferior oblique motoneurons. In conclusion, combined immunostaining for parvalbumin, perineuronal nets and calretinin may well be suited for the specific identification and subsequent analysis of premotor upgaze pathways in clinical cases of isolated up- or downgaze deficits.